Low income is associated with poor adherence to a Mediterranean diet and a higher prevalence of obesity: cross-sectional results from the Moli-sani study - Bonaccio, Marialaura (BMJ Publishing Group, 2012)
OBJECTIVES: To examine cross-sectional associations of socioeconomic status (ie, income and education) with an adherence to a Mediterranean dietary pattern and obesity prevalence. DESIGN: Cross-sectional study on a sample of Italian subjects enrolled in the Moli-sani Project, a population-based cohort study. The Italian EPIC food frequency questionnaire was used to determine food intake. Adherence to a Mediterranean diet (MD) was appraised according to both the Mediterranean score elaborated by Trichopoulou (MDS) and the novel Italian Mediterranean Index (IMI) and to the a posteriori scores derived from principal component analysis. Four income categories were identified. SETTING: Molise region, Italy. PARTICIPANTS: 13 262 subjects (mean age 53±11, 50% men) out of 24 318 citizens (age ≥35) randomly enrolled in the Moli-sani Project. MAIN OUTCOMES: Dietary patterns and risk factors for cardiovascular disease. RESULTS: Household higher income were significantly associated with greater adherence to an MD (p<0.0001) and to Olive oil and Vegetables dietary pattern in a multivariable model including age, sex, daily energy intake, body mass index, physical activity, smoking, alcohol consumption, education and marital status. The odds of having the highest adherence to an MD clearly increased according to income levels. People having the highest income had 54% (95% CI 21% to 97%, MDS) or 72% (95% CI 34% to 121%, IMI) higher probability to stick to an MD-like eating pattern than those in the lowest-income group. Obesity prevalence was higher in the lowest-income group (36%) in comparison with the highest-income category (20%, p<0.0001). Income was associated with dietary patterns in all categories of education. CONCLUSIONS: A higher income and education are independently associated with a greater adherence to MD-like eating patterns and a lower prevalence of obesity.